Slow walking model for children with multiple disabilities via an application of humanoid robot. (February 2016) - Wang, ZeFeng; Peyrodie, Laurent; Cao, Hua; Agnani, Olivier; Watelain, Eric; Wang, HaoPing
Abstract: Walk training research with children having multiple disabilities is presented. Orthosis aid in walking for children with multiple disabilities such as Cerebral Palsy continues to be a clinical and technological challenge. In order to reduce pain and improve treatment strategies, an intermediate structure – humanoid robot NAO – is proposed as an assay platform to study walking training models, to be transferred to future special exoskeletons for children. A suitable and stable walking model is proposed for walk training. It would be simulated and tested on NAO. This comparative study of zero moment point (ZMP) supports polygons and energy consumption validates the model as more stable than the conventional NAO. Accordingly direction variation of the center of mass and the slopes of linear regression knee/ankle angles, the Slow Walk model faithfully emulates the gait pattern of children. Abstract : Highlights: A Slow Walking model is proposed for the children with multiple disabilities. In order to reduce pain and improve treatment strategies, humanoid robot NAO is proposed as an intermediate assay platform. In Slow Walking model, the knees are intermittent straight, which is more like human walking. In comparison with NAO conventional walking model in ZMP supports polygons, Slow Walking model is more stable. Slow Walking model consumes less energy.